2019
DOI: 10.3889/oamjms.2019.537
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate Due to Circulatory and Alcohol-Dependent Diseases in Different Climatic Zones of Russia

Abstract: AIM: Evaluation of the impact of climatic factors on the formation of mortality due to circulatory diseases and a group of diseases related to alcohol consumption identified as alcohol-dependent. METHODS: The study subject was the adult population residing in different climatic zones of Russia: in the second, third and fourth zones, with different conditions: average annual temperature (5.2°C; 1-2°C; -2.0°C), snow cover duration (≤ 150 days, ≤ 180 days, ≈ 220 days) sunshine duration and the presence of polar n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Many epidemiological studies have provided evidence of the relationship between morbidity, mortality and environmental temperature (Åström et al, 2019;Yakovleva et al, 2019), and mortality caused by low temperature is much higher than that caused by high temperature (Gasparrini et al, 2015;Shor & Roelfs, 2019;Zhan et al, 2017). It has been suggested that the risk of respiratory diseases increases significantly when the external temperature decreases, especially in the elderly (Bunker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have provided evidence of the relationship between morbidity, mortality and environmental temperature (Åström et al, 2019;Yakovleva et al, 2019), and mortality caused by low temperature is much higher than that caused by high temperature (Gasparrini et al, 2015;Shor & Roelfs, 2019;Zhan et al, 2017). It has been suggested that the risk of respiratory diseases increases significantly when the external temperature decreases, especially in the elderly (Bunker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%